Perceptions of Grandparents About Challenges and Opportunities in Transferring Traditional Knowledges to Their Overseas Grandchildren - Thapa, Nirajan (2024)
This study explores the impacts of migration on intergenerational relationship, particularly emphasizing on the dynamics of transnational grandparenting. As the most evident impact of migration on family structure has duly resulted in changing the role of grandparents; this study further investigates both the opportunities and constraints that grandparents face while performing their role in a transnational context.